1981
DOI: 10.1021/ja00394a034
|View full text |Cite
|
Sign up to set email alerts
|

Conformational analysis of the C(6)-O(1)-C(5)-C(4) fragment in acetylcholine by carbon-13 NMR spectroscopy

Abstract: We sought a thiocarbonyl reagent that could be introduced by simple acylation. A second consideration was that the intermediate radical species resulting from attack of tin at thione sulfur would not be stabilized at the a-carbon. Such a stabilization could allow abstraction of hydrogen from the trialkylstannane to compete effectively with alkyl carbon-oxygen bond homolysis. Dethiation (thiobenzoyl esterbenzyl ether) and collapse (dithiocarbonate esteralcohol starting material) byproducts have been observed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

1981
1981
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 7 publications
(9 reference statements)
2
11
1
Order By: Relevance
“…This result is in disagreement with a series of experimental studies [7,8,19,20] in which it was observed that the s 2 dihedral is often in the gauche conformation. The reason for which the gauche conformation should be favoured was justi®ed by invoking that``ACh + can be considered a member of a class of 1,2-disubstituted ethanes in which the increased stability of the gauche conformation is the norm.…”
Section: In Vacuocontrasting
confidence: 98%
“…This result is in disagreement with a series of experimental studies [7,8,19,20] in which it was observed that the s 2 dihedral is often in the gauche conformation. The reason for which the gauche conformation should be favoured was justi®ed by invoking that``ACh + can be considered a member of a class of 1,2-disubstituted ethanes in which the increased stability of the gauche conformation is the norm.…”
Section: In Vacuocontrasting
confidence: 98%
“…13CNMR experiments have shown that the dihedral angle, D 2, may attain both a gauche and a trans conformation in aqueous solution, with a rotamer population of 0.335/0.665 (Cassidei and Sciacovelli, 1981). However, the free-energy difference between these rotamers was calculated to be less than 0.5 kcal/mol, based on the rotamer population.…”
Section: Discussionmentioning
confidence: 99%
“…~3C NMR experiments have confirmed that the dihedral angle, D 2, may attain either a trans or a gauche position, and have indicated that the energy difference between these conformations is less than 0.5 kcal/mol (Cassidei and Sciacovelli, 1981). Other NMR experiments have demonstrated a maximum energy barrier of 7.9 kcal/mol for rotation about dihedral D 3 (Fig.…”
Section: Introductionmentioning
confidence: 87%
“…To understand the interactions of biologically interesting molecules, it is necessary to know the shape of the interaction sites as well as the conformations of the interacting molecules and, the conformational analysis of Ach has been subject of many experimental 6–25 and theoretical 26–46 investigations. Aspects of the Ach potential energy surface (PES) have been the subject of numerous experimental investigations including X‐Ray 6–8, 16–21, NMR 9, 11–14, 23, 25, electron diffraction 22, and Raman Spectroscopy 15, in addition, computational studies have employed ab initio 3, 31, 34, 35, 42–44, semi empirical and empirical methods 26–30, 38, 39 as well as molecular dynamics 36, 37, 45.…”
Section: Introductionmentioning
confidence: 99%